การพัฒนากระบวนการเรียนรู้แบบมีส่วนร่วมตามหลักวิถีชีวิตสีเขียวเพื่อเสริมสร้างสุขภาวะของครอบครัว - ยุรนันท์ ตามกาล (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This research study aimed to (1) study and analyze fundamental details of green family by using in-depth interviews and participant observations to collect data from 5 ideal green families living in Bangkok Metropolitan Region, and (2) develop participatory learning process based on green living principles to enhance family well-being by conducting a participatory research between a researcher and 3 experimental families, using family project and focus group discussion to collect data from the experimental families over the period of 6 months, during September 2016 - March 2017. The results were as follows: Objective 1: The fundamental details of green families were 1) Family Background; healthy relationship between family members, efficient household space management, general knowledge or personal interests that can be used to support green living lifestyle; 2) Motivation; health problems, acknowledgement of environmental problems, interestedness in agriculture; 3) Green lifestyle practicing; treatment of self and others, balanced environmental treatment; 4) Green lifestyle learning; joint learning of family members; 5) Family overall health status; improvement in physical, mental and social health; and 6) Family learning process consisted of 9 stages (e.g., motivation caused by health problems; knowledge gathering; activities practicing; further knowledge seeking from learning centers or from family member’s experiences when facing obstacles, and etc.). Objective 2: A learning process based on green living to enhance well-being of families consisted of 3 stages as follows; 1) learning to start making changes 2) learning to embrace or change mindset or mode of practice 3) learning from the results of those changes. Each stage contained various factors and conditions which can assist or hinder that particular learning process. Factors: family’s openness to learning together; good family communication, and etc.; conditions: healthy relationship between family members; continuing practices. This research created new knowledge on green living lifestyle and fundamental details of green families based on academic principles. Besides, the study provided knowledge on learning process based on green living to enhance well-being of families which will be useful to any individuals, families, communities, and organizations in pursuing green living lifestyle.